Faktor-Faktor Pembentuk Minat Berwirausaha Mahasiswa dengan Efikasi Diri sebagai Mediator - Wiranata, Evelin; Ida Puspitowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to empirically examine the influence of family environment and entrepreneurial knowledge on students’ entrepreneurial interest, with self-efficacy acting as a mediating variable. This research adopts a quantitative approach using purposive sampling. The sample consists of 201 students from three universities in West Jakarta. Data were collected through questionnaires distributed via Google Forms and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS version 4 software. The results indicate that the family environment has a negative and insignificant effect on entrepreneurial interest, while it has a positive and significant effect on self-efficacy. Entrepreneurial knowledge has a positive and significant influence on both self-efficacy and entrepreneurial interest. Self-efficacy also positively and significantly affects students’ entrepreneurial interest. Furthermore, self-efficacy mediates the relationship between family environment and entrepreneurial knowledge and entrepreneurial interest. Overall, the findings highlight that self-efficacy plays an important role in strengthening students’ entrepreneurial interest. Keywords: Entrepreneurial Knowledge, Family Environment, Interest in Entrepreneurship, Self-Efficacy.